2015
DOI: 10.1249/mss.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Quadriceps Femoris Hypertrophy in Response to Strength and Power Training

Abstract: These observed inhomogeneous changes in CSA may alter the thigh's moment of inertia and moment arms of muscle "compartments," and the influence of elastic component force transmission on the muscular force expression. Such selective hypertrophy is speculated to be biomechanically beneficial to high-force or high-power movements used in training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 37 publications
5
107
2
5
Order By: Relevance
“…This would be due to that (a) sufficient (2‐minutes) rest periods were taken between sets, and (b) each contraction was brief (training velocity was fast). It is worth noting that several studies have shown evidence of hypertrophy after training composed of brief (explosive), unfatiguing contractions, given a certain level of mechanical stress (eg, ECC‐leg in this study). Therefore, it seems that fatigue/metabolic stress is not a necessary stimulus for muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This would be due to that (a) sufficient (2‐minutes) rest periods were taken between sets, and (b) each contraction was brief (training velocity was fast). It is worth noting that several studies have shown evidence of hypertrophy after training composed of brief (explosive), unfatiguing contractions, given a certain level of mechanical stress (eg, ECC‐leg in this study). Therefore, it seems that fatigue/metabolic stress is not a necessary stimulus for muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 72%
“…Nevertheless, the current result suggests that RF is indeed preferentially trained by single‐joint ECC knee extension training. Interestingly, the available literature suggests that resistance training comprising multi‐joint leg extensions (ie, simultaneous knee extension and hip extension) such as the squats, rowing, and cycling induces less hypertrophy in RF than the vasti. Precise mechanisms for such exercise modality‐dependent inter‐muscle differences in QF hypertrophy are unknown, but are probably mainly attributable to the difference between RF and the vasti being bi‐ and mono‐articular muscles, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this notion, Earp et al . () reported that parallel and jump squat training induced insignificant changes in CSA of RF despite significant increases in CSA of vasti.…”
Section: Discussionmentioning
confidence: 90%
“…A prática de exercícios na musculação pode proporcionar Revista Mundi Saúde e Biológicas. Curitiba, PR, v. 1, n. 2, 12, jul./dez., 2016 12-3 diversas adaptações no organismo como melhora da capacidade aeróbica (GETMANN e POLLOCK, 1981), aumento da força e da massa muscular (hipertrofia) (EARP et al, 2015). Além disso, devido ao fato da pratica da musculação demandar de aumento no gasto calórico, é possível a ocorrência de emagrecimento (WEISS et al, 2016).…”
Section: Introductionunclassified